"Two Faces See whoever looks at Him": The Appearance of "The Mythic Other" in the Play Beyond the Boundaries by J. H. Brenner - Hameiri, Israel (MiKAN, 2008)
The first part of this article presents J. H. Brenner’s play Beyond the Boundaries (London, 1907) as an important dramatic experiment. Although quite neglected by Israeli theatre and literary criticism, the play creates a unique style which can be defined as realistic-symbolic, a terminology used in the play by the protagonist writer Yohanan. Later, the article deals with some ethical and poetical ideas of Emmanuel Levinas as a basis for establishing the definition of a dramatic character, or type of character, which I call "The Mythic Other". In order to clarify the rhetorical and stylistic implications of the Mythic Other appearance, some Shakespearean characters are examined, as well as the "Rat Wife" which appears in Ibsen’s play Little Eyolf (1894). The comparison with Ibsen’s play accompanies the discussion of the Mythic Other in Brenner’s Beyond the Boundaries, Yohanan’s friend Eliyahu Hezkuni. Hezkuni portrays a combination of psychological and sexual otherness with mythic traits, which reflects the hero’s hidden self, and exposes the entire play as dealing with salvation through otherness.